2016
DOI: 10.1186/s12864-016-3188-y
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of psoriasis reveals biological pathways and roles for coding and long non-coding RNAs

Abstract: BackgroundPsoriasis is an immune-mediated, inflammatory disorder of the skin characterized by chronic inflammation and hyperproliferation of the epidermis. Differential expression analysis of microarray or RNA-seq data have shown that thousands of coding and non-coding genes are differentially expressed between psoriatic and healthy control skin. However, differential expression analysis may fail to detect perturbations in gene coexpression networks. Sensitive detection of such networks may provide additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 42 publications
2
68
0
1
Order By: Relevance
“…Increased mRNA levels of OR10G7 were recently detected by skin tape stripping in atopic dermatitis patients in the upper epidermal layers. Although this may constitute a potential mechanism of odorant-induced skin inflammation in AD patients [106,107], an earlier study found olfactory receptor genes to be downregulated in AD [40]. This may reflect the above-mentioned difficulties in inter-study comparison or may argue for the high diversity seen in the AD pathophysiology.…”
Section: Atopic Dermatitismentioning
confidence: 92%
See 1 more Smart Citation
“…Increased mRNA levels of OR10G7 were recently detected by skin tape stripping in atopic dermatitis patients in the upper epidermal layers. Although this may constitute a potential mechanism of odorant-induced skin inflammation in AD patients [106,107], an earlier study found olfactory receptor genes to be downregulated in AD [40]. This may reflect the above-mentioned difficulties in inter-study comparison or may argue for the high diversity seen in the AD pathophysiology.…”
Section: Atopic Dermatitismentioning
confidence: 92%
“…Utilizing weighted gene co-expression network analysis, long non-coding RNA (lncRNA) molecules were shown to be highly abundant in the psoriatic [165] and AD transcriptomes [166]. This high abundance paired with the observed treatment response potentially provides a molecular surrogate marker for successful treatment [107].…”
Section: Emerging Possibilities In Disease Studiesmentioning
confidence: 99%
“…Alternative splicing is prevalent in the mammalian immune system to control lymphocyte homeostasis (Yabas, Elliott, & Hoyne, 2016). Moreover, lncR-NAs regulate the inflammatory response following activation of innate immunity and have been related to autoimmune diseases such as psoriasis (Ahn et al, 2016;Heward & Lindsay, 2014). Interestingly, 25% of the annotated genes identified among the 30 1-mb non-overlapping windows most associated with IBH susceptibility correspond to lncRNAs.…”
Section: Associated Genomic Regions In This Studymentioning
confidence: 99%
“…The analysis of the molecular backdrop of psoriasis has described numerous disease-associated genes and proteins with abnormal expression patterns [3], but little is known about the regulatory pathways responsible for this aberrant expression. Recent findings suggest that non-coding RNAs such as microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) could be involved in the pathogenesis of psoriasis by influencing protein expression and function in both keratinocytes and inflammatory cells [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the molecular backdrop of psoriasis has described numerous disease-associated genes and proteins with abnormal expression patterns [3], but little is known about the regulatory pathways responsible for this aberrant expression. Recent findings suggest that non-coding RNAs such as microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) could be involved in the pathogenesis of psoriasis by influencing protein expression and function in both keratinocytes and inflammatory cells [4][5][6][7][8].Recent discoveries have let to the identification of a subclass of non-coding RNA, the circular RNAs (circRNAs), which are formed by a backsplicing event linking the 3′ end of an exon to the 5′ end of the same or an upstream exon [9][10][11]. Most circRNAs are expressed from known protein coding genes and in human cells more unique circRNAs than genes have been annotated [12].…”
mentioning
confidence: 99%